Validation of a novel drug target in type 2 diabetes mellitus - Alexandersson, Ida (My University, 2017)
Type 2 diabetes (T2DM) is characterized by altered insulin secretion as a result of progressive functional failure of pancreatic -cells. Genetics is known to be a factor in the pathophysiolgy of the disease, and several genomic loci have been identified with T2DM susceptibility. Polymorphisms in the gene encoding Target X is associ-ated with T2DM and the expression of the gene is further upregulated in pancretic T2DM -cells. In this study, the mechanism linking an increased expression of Target X to T2DM was evaluated. Overexpression of Target X was achieved with adenoviral transduction. The gene was overexpressed in two -cell lines, EndoC- H1 and MIN6. Functional assays evaluating glucose stimulated insulin secretion (GSIS), proliferation and apoptosis in response to ovrexpressing Target X were per-formed with both cell lines. Upregulated gene expression of Target X in EndoC- H1 cells resulted in a reduction in cytokine induced apoptosis compared to control. Moreover, it returned an increased fold-response in GSIS. Even though a trend of increased apoptosis was observed with the MIN6 cells, there was no significant dif-ference compared to control samples. Contrary to the results with EndoC- H1 cells, a significant decrease in fold-response in the GSIS assay was observed with MIN6 cells. No impact of overexpression of Target X on proliferation was observed with any of the two cell lines. Nevertheless, qPCR analyses revealed a low fold increase in mRNA expression in MIN6 cells compared to EndoC- H1 cells. In conclusion, this study gave further insight into the linkage between upregulation of Target X and T2DM by suggesting that it may influence -cell survival and insulin secretion.
Keywords: Cellbiologi; Immunologi; Cell- och molekylärbiologi; Livsvetenskaper; Cell Biology; Immunology; Cell and Molecular Biology; Life Science